2004
DOI: 10.1093/bioinformatics/bth142
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy J-Means and VNS methods for clustering genes from microarray data

Abstract: The source code of the clustering software (C programming language) is freely available from Nabil.Belacel@nrc-cnrc.gc.ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…The exact F-KM formalism is described in detail elsewhere( [15,16] and references therein). Briefly, the membership values and the centroid positions are calculated from the objective function J m (W, V)definedas…”
Section: Fuzzy K-means Clustering Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…The exact F-KM formalism is described in detail elsewhere( [15,16] and references therein). Briefly, the membership values and the centroid positions are calculated from the objective function J m (W, V)definedas…”
Section: Fuzzy K-means Clustering Methodologymentioning
confidence: 99%
“…For the NMR spectral profiles of cell lines clustered using F-KM into five sample clusters: R i = 0.80 for absolute value distances; R i = 0.74 for Euclidian distance matrix and R i = 0.75 for cosine dissimilarity matrix. The degree of fuzziness in the clustering process is regulated by the fuzziness parameter, m,w i t hm = 1 giving the crisp clustering and with an increasing fuzziness of the result with m increasing ultimately leading to clustering result for all points being w ik = 1/c for all i and k. A previously devised empirical rule about the optimal m parameter [15,24] suggests that an optimal m value should lead to (i) the median of the top membership values being ≥0.5 (prevents the results from being overly fuzzy) and (ii) the median of all membership values being ≥0 (prevents the results from becoming crisp). The analysis has shown that for these datasets an optimal value of m is 2, which is in agreement with the value originally suggested by Bezadek [16] for the general application of F-KM.…”
Section: Fuzzy K-means Clustering Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…This way of partition is more realistic in labeling the regions of foreground spots from the background as well as from possible artifacts. The fuzzy c-means (FCM) based approaches have been introduced for several microarray data analysis [26][27][28][29][30]. In [26,30] FCM was used for grouping biologically relevant genes.…”
Section: Clustering Based Approachesmentioning
confidence: 99%